2020
DOI: 10.3174/ajnr.a6394
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Mean Upper Cervical Cord Area Implementation in a Longitudinal MRI Setting: Methods, Interrater Reliability, and MRI Quality Control

Abstract: BACKGROUND AND PURPOSE: Spinal cord atrophy is commonly measured from cerebral MRIs, including the upper cervical cord. However, rescan intraparticipant measures have not been investigated in healthy cohorts. This study investigated technical and rescan variability in the mean upper cervical cord area calculated from T1-weighted cerebral MRIs. MATERIALS AND METHODS: In this retrospective study, 8 healthy participants were scanned and rescanned with non-distortionand distortion-corrected MPRAGE sequences (11-50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In addition to the biological-derived normalization strategy, previous studies have reported a variability in CSA measures associated with the MRI acquisition parameters, and segmentation method (Kearney et al, 2014 ; Papinutto and Henry, 2019 ; Chien et al, 2020 ; Cohen-Adad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the biological-derived normalization strategy, previous studies have reported a variability in CSA measures associated with the MRI acquisition parameters, and segmentation method (Kearney et al, 2014 ; Papinutto and Henry, 2019 ; Chien et al, 2020 ; Cohen-Adad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond IMA, the need for QC has been recognized for other technical procedures. In the context of MS research, magnetic resonance imaging and optical coherence tomography serve as examples for which recommendations have been made regarding standardized protocols, QC, and harmonious reporting thereof [ 38 - 42 ]. Therefore, we propose standardized reporting of IMA results to include information regarding the following: (1) number of recording failures during data acquisition; (2) type and amount of applied postprocessing, both technical and manual; (3) fraction of recordings undergoing QC; (4) fraction of recordings ultimately excluded from analysis (mention of respective causes would be highly valuable for future users)…”
Section: Discussionmentioning
confidence: 99%
“…Beyond IMA, the need for QC has been recognized for other technical procedures. In the context of MS research, magnetic resonance imaging and optical coherence tomography serve as examples for which recommendations have been made regarding standardized protocols, QC, and harmonious reporting thereof [38][39][40][41][42]. Therefore, we propose standardized reporting of IMA results to include information regarding the following: (1) number of recording failures during data acquisition; (2) type and amount of applied postprocessing, both technical and manual; (3) fraction of recordings undergoing QC; (4) fraction of recordings ultimately excluded from analysis (mention of respective causes would be highly valuable for future users)…”
Section: Discussionmentioning
confidence: 99%